Arabidopsis 4-COUMAROYL-COA LIGASE 8 contributes to the biosynthesis of the benzenoid ring of coenzyme Q in peroxisomes. Issue 22 (27th November 2019) - Soubeyrand, Eric; Kelly, Megan; Keene, Shea A.; Bernert, Ann C.; Latimer, Scott; Johnson, Timothy S.; Elowsky, Christian; Colquhoun, Thomas A.; Block, Anna K.; Basset, Gilles J.
Abstract : Plants have evolved the ability to derive the benzenoid moiety of the respiratory cofactor and antioxidant, ubiquinone (coenzyme Q), either from the β-oxidative metabolism of p -coumarate or from the peroxidative cleavage of kaempferol. Here, isotopic feeding assays, gene co-expression analysis and reverse genetics identified Arabidopsis 4-COUMARATE-COA LIGASE 8 ( 4-CL8 ; At5g38120 ) as a contributor to the β-oxidation of p -coumarate for ubiquinone biosynthesis. The enzyme is part of the same clade (V) of acyl-activating enzymes than At4g19010, a p -coumarate CoA ligase known to play a central role in the conversion of p -coumarate into 4-hydroxybenzoate. A 4-cl8 T-DNA knockout displayed a 20% decrease in ubiquinone content compared with wild-type plants, while 4-CL8 overexpression boosted ubiquinone content up to 150% of the control level. Similarly, the isotopic enrichment of ubiquinone's ring was decreased by 28% in the 4-cl8 knockout as compared with wild-type controls when Phe-[ Ring- 13 C6 ] was fed to the plants. This metabolic blockage could be bypassed via the exogenous supply of 4-hydroxybenzoate, the product of p -coumarate β-oxidation. Arabidopsis 4-CL8 displays a canonical peroxisomal targeting sequence type 1, and confocal microscopy experiments using fused fluorescent reporters demonstrated that this enzyme is imported into peroxisomes. Time course feeding assays using Phe-[ Ring- 13 C6 ] in a series of Arabidopsis single and double knockouts blocked in the β-oxidative metabolism of p -coumarate ( 4-cl8; at4g19010; at4g19010 × 4-cl8), flavonol biosynthesis ( flavanone-3-hydroxylase ), or both ( at4g19010 × flavanone-3-hydroxylase ) indicated that continuous high light treatments (500 µE m −2 s −1 ; 24 h) markedly stimulated the de novo biosynthesis of ubiquinone independently of kaempferol catabolism.